PENGARUH PENERAPAN MODEL PICTURE AND PICTURE PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA SMA - Eva Fitriyani; Parijo Parijo; Putri Tipa Anasi (Universitas Tanjungpura, 2019)
Abstract The purpose of this research was to find out the effect of using picture and picture model in teaching geography to students Class XI Social SMA Taruna Bumi Khatulistiwa Kubu Raya Regency. The method used was Experiment method in form of Quasi Experiment design and Nonequivalent Control Group Research Design. The population was the whole 118 students of class XI, with the sample of 31 students from class XI Social 1 as the experiment class and 25 students from class XI Social 2 as the control class. The result was the average of the Control class was 76,44 and the average of the Experiment class was 85,13. From the result of the test from T-test showed the value of tcount of3,9031 and the ttable (α = 5%) of 1,6749, meaning that tcount (3,9031) > ttable (1,6749), therefore, Ha is accepted. In conclusion, there is an effect of using picture and picture cooperative model in teaching geography to the students Class XI Social. The value of Effect Size (ES) was 0,84 (category high). Based on the value obtained, it can be said that the application of Picture and Picture Model gave positive impact to Students Class XI Social.Keywords: impact, Picture and Picture Model, Learning Result, Geography